Conformational analysis and interaction of the Staphylococcus aureus transmembrane peptidase AgrB with its AgrD propeptide substrate - Bardelang, Philip; Murray, Ewan J.; Blower, Isobel; Zandomeneghi, Sara; Goode, Alice; Hussain, Rohanah; Kumari, Divya; Siligardi, Giuliano; Inoue, Katsuaki; Luckett, Jeni; Doutch, James; Emsley, Jonas; et al. (Frontiers in Chemistry, 2023)
Virulence gene expression in the human pathogen, S. aureus is regulated by the agr (accessory gene regulator) quorum sensing (QS) system which is conserved in diverse Gram-positive bacteria. The agr QS signal molecule is an autoinducing peptide (AIP) generated via the initial processing of the AgrD pro-peptide by the transmembrane peptidase AgrB. Since structural information for AgrB and AgrBD interactions are lacking, we used homology modelling and molecular dynamics (MD) annealing to characterise the conformations of AgrB and AgrD in model membranes and in solution. These revealed a six helical transmembrane domain (6TMD) topology for AgrB. In solution, AgrD behaves as a disordered peptide, which binds N-terminally to membranes in the absence and in the presence of AgrB. In silico, membrane complexes of AgrD and dimeric AgrB show non-equivalent AgrB monomers responsible for initial binding and for processing, respectively. By exploiting split luciferase assays in Staphylococcus aureus, we provide experimental evidence that AgrB interacts directly with itself and with AgrD. We confirmed the in vitro formation of an AgrBD complex and AIP production after Western blotting using either membranes from Escherichia coli expressing AgrB or with purified AgrB and T7-tagged AgrD. AgrB and AgrD formed stable complexes in detergent micelles revealed using synchrotron radiation CD (SRCD) and Landau analysis consistent with the enhanced thermal stability of AgrB in the presence of AgrD. Conformational alteration of AgrB following provision of AgrD was observed by small angle X-ray scattering from proteodetergent micelles. An atomistic description of AgrB and AgrD has been obtained together with confirmation of the AgrB 6TMD membrane topology and existence of AgrBD molecular complexes in vitro and in vivo.